HASIL BELAJAR KOGNITIF BIOLOGI DIPREDIKSI DARI EMOTIONAL QUOTIENT (EQ) DAN KESIAPAN BELAJAR SISWA KELAS X SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2011/2012 - Hermita, Resty; Karyanto, Puguh; Rosyidi, Alvi (Pendidikan Biologi, 2012)
ABSTRACT ? The aims of this research  are  certain the relationship of 1)  emotional quotient (EQ) with student?s cognitive learning achievement of biology in X grade of SMA Negeri 7 Surakarta in academic year 2011/2012, 2) learning  readiness with student?s cognitive  learning  achievement of biology in  X grade of SMA Negeri 7 Surakarta in academic year 2011/2012, 3) emotional quotient (EQ) and learning readiness with student?s cognitive  learning achievement of biology  in X grade of SMA Negeri 7 Surakarta in academic year 2011/2012. This was a correlational quantitive research. The population were all of the students in X grade of SMA Negeri 7 Surakarta in academic year of 2011/2012. The sample was taken among 74 samples of student using  simple random sampling  technique. The data was collected by  test, documentation, and questionnaire. Test was used to knowing  student?s  emotional quotient  (EQ), documentation was used to getting student?s cognitive learning achievement, and learning readiness was measured by using questionnaire. Analyze uses correlation regression analysis with SPSS 17. The result showed that  1) there  is  a relationship  between  emotional quotient (EQ) and student?s cognitive learning achievement of biology in X grade of SMA Negeri 7 Surakarta in academic year 2011/2012, 2) there is a relationship between  learning  readiness  and  student?s cognitive  learning  achievement  of biology in X grade of SMA Negeri 7 Surakarta in academic year 2011/2012, 3) there is a relationship both of  emotional quotient  (EQ)  and   learning  readiness with  student?s cognitive  learning  achievement  of biology in  X grade of SMA Negeri 7 Surakarta in academic year 2011/2012.  The three aforementioned correlation are considered as significant and positive valuable. Keywords:  Emotional Quotient  (EQ),  learning readiness,  cognitive learning outcome of biology, correlation regression analysis